Plummer Vinson syndrome in children: case series - Sethuraman, Chidambaram; Bavanandam, Sumathi; Dheivamani, Nirmala; B., Bhaskar Raju (International Journal of Contemporary Pediatrics, 2017)
Plummer Vinson syndrome (PVS) is a rare entity in children and classically presents with a triad of anemia, dysphagia and post cricoid web. We report four paediatric cases of PVS reported in a tertiary care institute in Chennai, India over a period of 6 years. All children were above 5 years of age with M:F of 1:3. Mean duration of symptomatology was 13.5 months. Mean age at the diagnosis was 9.3 years. Classical triad of PVS was seen in all of our children who responded well to endotherapy without any recurrence. Though rare in children case series of PVS are highlighted to stress the importance of evaluation, when children present with dysphagia and anemia and the necessity of early referral to paediatric GI centre for successful management.